Legal Impact Of Catcalling Perpetrators And Physiological Impact On Victims In Indonesia - Putrawan, I Nyoman Alit; Tagel, Dewa Putu (Ipso Jure, 2024)
This article aims to provide a comprehensive understanding of the legal framework related to catcalling perpetrators and their physiological impact on victims in Indonesia as well as more effective law enforcement efforts in tackling this phenomenon. The focus is on increasing awareness of legal protection for victims and supporting stronger law enforcement against perpetrators of catcalling. In the research context, catcalling often occurs in open public places, especially with the majority of victims being women who wear the hijab. Forms of catcalling include comments, teasing, gestures, and touching. The research method used is qualitative with a literature review study approach. Data regarding catcalling cases was obtained from the researcher's personal experience, supported by journal research highlighting similar cases in Indonesia. Catcalling is a serious form of sexual harassment, with detrimental impacts on victims such as feelings of insecurity and emotional stress. Strong legal protection, public awareness, and more specific regulations are needed to address this problem effectively. With these steps, it is hoped that we can create a safer environment and respect individual rights. In order to deal with the problem of catcalling, there needs to be a synergy between strengthening the existing legal framework, outreach campaigns, and improving regulations governing behavior in public spaces. In addition, the importance of support from authorities such as the police and other law enforcement agencies to ensure that catcalling cases are handled seriously and fairly. In addition, there is a need for a holistic approach that involves providing psychological and social support for victims to help them recover from the impact of the trauma they may have experienced. Overall, efforts to overcome the catcalling phenomenon require collaboration between the government, the community and various other stakeholders. Only with comprehensive and coordinated measures can we create a safer environment that respects individual rights, and prevent the recurrence of catcalling cases in the future.